Atoning in purgatory. Issue 2 (28th July 2016) - THUROW, JOSHUA C.
Abstract: This article develops a new argument – The Argument from Atonement – that commonplace Christian assumptions about heaven imply the existence of purgatory. According to this argument, many Christians will die with residual moral guilt due to possessing unfulfilled moral debts towards fellow non-divine humans. Some of these debts cannot be fulfilled immediately after death and are not completely fulfilled or cancelled by Jesus's atoning work. Christians with such debts are fit neither for heaven nor for hell and thus must occupy purgatory until their moral debts are fulfilled.